Unleashing the Power of OpenAI in Shaping the Future of Cancer Research - Ramyar M. Abdullah; Hawro D. I. Masseh; Abbas Salihi; Bawar Mohammed Faraj (QAASPA Publisher, 2023)
Artificial intelligence (AI) is rapidly changing cancer research and treatment development. OpenAI, a pioneer in AI research, is at the vanguard of this revolution. This review article highlights the potential of OpenAI to shape the future of cancer research, including the identification of new therapeutic targets, predictive modeling for cancer progression and response to therapy, the development of personalized treatment plans, and advancements in drug discovery and development. The article also discusses the challenges of implementing OpenAI in cancer research and incorporating AI into the research process. Finally, the article concludes with a discussion of AI's future prospects in cancer research, as well as future research recommendations.